Bailey's Industrial Oil and Fat Products 2020
DOI: 10.1002/047167849x.bio026.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Linolenic Acid: Sources and Functions

Abstract: Gamma‐linolenic acid (GLA, cis 6, cis 9, cis 12‐octadecatrienoic acid) is a conditionally essential fatty acid of the n‐6 family. It is produced in the mammalian body from enzymatic desaturation of linoleic acid, an essential fatty acid that must be supplied by the diet. It is widely distributed in plant kingdom in trace amounts, and is not present in major commercial vegetable seed oils. It is present in seeds of many species belonging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 176 publications
0
3
0
Order By: Relevance
“…Oenothera biennis L., evening primrose), Boraginaceae (Borago officinalis L., borage), Grossulariaceae (Ribes nigrum L. black currant), Malvaceae (Durio graveolens Becc. ), Cannabaceae (Cannabis sativa L., hemp) produce substantial amounts (7-20%) of this fatty acid as a constituent of their seed oils (PlantFAdb 2016;Guil-Guerrero et al 2001;Alonso-Esteban et al 2020;Kapoor and Nair 2020). In addition to higher plant species, γlinolenic acid has been also detected in animals, protozoa, fungi, algae and mosses.…”
Section: Phytochem Revmentioning
confidence: 99%
See 1 more Smart Citation
“…Oenothera biennis L., evening primrose), Boraginaceae (Borago officinalis L., borage), Grossulariaceae (Ribes nigrum L. black currant), Malvaceae (Durio graveolens Becc. ), Cannabaceae (Cannabis sativa L., hemp) produce substantial amounts (7-20%) of this fatty acid as a constituent of their seed oils (PlantFAdb 2016;Guil-Guerrero et al 2001;Alonso-Esteban et al 2020;Kapoor and Nair 2020). In addition to higher plant species, γlinolenic acid has been also detected in animals, protozoa, fungi, algae and mosses.…”
Section: Phytochem Revmentioning
confidence: 99%
“…γ-Linolenic acid is classified as a "conditionally essential fatty acid", because it becomes essential to humans in some specific health conditions. Several scientific studies have demonstrated that a high intake of ω-6 fatty acids such as γ-linolenic acid is beneficial to human health since its endogenous formation in the human body is low or impaired in some pathological conditions including diabetes, atopic dermatitis, cardiovascular disease, rheumatoid arthritis and cancer (Fan and Chapkin 1998;Belch and Hill 2000;Kapoor and Huang 2006;Kawamura et al 2011;Simon et al 2014;Kapoor and Nair 2020). Reduction of the synthesis of γ-linolenic acid also limits the physiological production of dihomo-γlinolenic and arachidonic acids with the consequent decrease in the formation of eicosanoids (prostaglandins, prostanoids and prostacyclins), important cell signalling molecules involved in several physiological and pathological processes.…”
Section: Phytochem Revmentioning
confidence: 99%
“…Few plant sources have been used for commercial GLA production, mainly in health food, pharmaceutical, pet food and cosmetic industries. These sources include oils from borage, evening primrose, black currant and, more recently, hemp (10) . The GLA treatment effectively inhibits the growth of gastric cancer cells in hypoxia.…”
mentioning
confidence: 99%